Geomatics and Ancient Architecture: the study of Villa San Marco and the Baths of Stabiae - Dario Saggese (Groma, 2023)
In recent decades, archaeological research has increasingly made use of geomatic techniques to document ancient spaces and sites. The topographical research carried out in 2018 by the University of Bologna at Villa San Marco and the adjacent thermal complex in Castellammare di Stabia adopted the terrestrial laser scanner technology. It allowed the restitution of a three-dimensional model for an in-depth study of the architectural structure of the building and its construction phases, as well as the production of an updated planimetry of both complexes and wall elevation orthophotos useful for understanding the conservation status of the monument. This study is part of the ‘Piano della Conoscenza di Stabiae'